Patient-related factors associated with medication adherence behavior in patients with end-stage renal disease: A systematic review - Anis A'lliya, Latif *; Lee, Kai Wei; Aneesa, Abdul Rashid; Chan, Nee Nee *; Peh, Suat Cheng *; Thiruventhiran, Thilaganathan; Ooi, Pei Boon * (Medknow Publications, 2022)
Objectives: This systematic review aims to identify influencing factors of medication adherence behavior in patients with end-stage renal disease (ESRD), with a special interest in patient-related factors based on the World Health Organization adherence model.